Novejši procesi v prostorskem razvoju Maribora - Rebernik, Dejan (Geografski vestnik, 2009)
The paper is based on the results of research project "Linking policies and criteria for achieving the sustainable spatial development of towns and other settlements in functional urban areas", which was carried out in 2007 and 2008 by researchers of Department of Geography at Faculty of Arts of University in Ljubljana and Urban Planning Institute of the Republic of Slovenia. The paper presents only a part of the results of the research project, predominantly the analysis of trends and processes of spatial development in Maribor. Maribor and its urban region was chosen as a case study area in the research project. The main goal of the paper is to describe the most prominent process in spatial urban development of Maribor and at the same time to highlight the discordance between the goals and objectives of spatial policies and actual urban development.
Keywords: urbana geografija; mesta; prostorski razvoj; stanovanjska naselja; Slovenia; Slovenija; Maribor